A Revolution called Intellectual Property - Fernández Méndez, Colin (2017)
Revolutions are like Saturn, which devour their own children; a saying designed in correspondence with one of the most merciless gods of roman mithology, where no revolution was known without destruction or violence, seeking a change through violence; apart from taking victims opponents, it took the same revolutionaries when their own violence unleashed would turn against themselves.Those revolutions, which are frozen in the past for historical records, are today being replaced by one that increases in validity and authenticity. A Revolution that does not need to destroy to transform lives, to revive hopes and to transmit enthusiasm to its most fascinated followers, and even to those who still maintain themselves skeptics. On the contrary, it needs to create, invent and innovate in order to achieve its real and original mission.Creations with identity and defense guaranteed by a revolution called Intellectual Property, for instance, airplanes of the early twentieth century; antibiotics such as penicillin in the 1940s and streptomycin in the 1950s; as well as the so-called semiconductors, of around half of the twentieth century, which themselves transformed the modus vivendi and considerably increased life expectancy and quality of life of millions of people worldwide. Gathering all these revolutionary inventions of the recent past together with the current inventions which are already patented, being among the most representative piece, 3D and 4D printers; and those related to nanotechnology’s inventions; and those that belong to robotics, which promise without ambiguity, to continue to achieve the goal. Revolutionize humanity.